Comparative study of rise of vitamin D in hypovitaminosis D babies after two different dosage recommendations - Shrivastava, Bijal; Aryan, Rashi; Tiwari, Abhinav; Tiwari, Lekha; Pravallika, Nimmkayala (International Journal of Contemporary Pediatrics, 2018)
Background: There are currently two different guidelines for treatment of Vitamin D deficiency in infants, one is that of American Academy of Pediatrics and the other being Clinical Practice Guidelines of the Endocrine Society. This study was done to compare the two guidelines for treatment of Vitamin D deficiency in infants. Methods: A hospital based, longitudinal interventional study was conducted for 2 years and 115 babies having vitamin d deficiency (Vitamin D less than or equal to 20ng/dl) were divided into group A and group B. Group A babies were treated as per American Academy of Pediatrics Guidelines whereas Group Cases were treated as per International Endocrine Society guidelines. All babies were followed up after 3-4 months when repeat Vitamin D levels were checked and then compared. Results: In present study, Vitamin D level had increased by 0.6 times in Group A whereas it had increased by 1.3 times in group B and it was significant. Conclusions: Study results were in favour of the guidelines recommended by the International Endocrine Society.